Host Lipids in Positive-Strand RNA Virus Genome Replication - Zhang, Zhenlu; He, Guijuan; Filipowicz, Natalie A.; Randall, Glenn; Belov, George A.; Kopek, Benjamin G.; Wang, Xiaofeng (Frontiers in Microbiology, 2019)
Membrane association is a hallmark of the genome replication of positive-strand RNA viruses [(+)RNA viruses]. All well-studied (+)RNA viruses remodel host membranes and lipid metabolism through orchestrated virus-host interactions to create a suitable microenvironment to survive and thrive in host cells. Recent research has shown that host lipids, as major components of cellular membranes, play key roles in the replication of multiple (+)RNA viruses. This review focuses on how (+)RNA viruses manipulate host lipid synthesis and metabolism to facilitate their genomic RNA replication, and how interference with the cellular lipid metabolism affects viral replication.